2006
DOI: 10.1532/ijh97.05124
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Conditioning Followed by Unrelated Umbilical Cord Blood Transplantation for Advanced Hematologic Malignancies: Rapid Engraftment in Bone Marrow

Abstract: Reduced-intensity (RI) conditioning followed by cord blood transplantation (CBT) is a new treatment modality, but failure to engraft is a major concern. We describe 12 patients with advanced hematologic malignancies who underwent RI conditioning and CBT with a conditioning regimen consisting of 200 mg/m(2) fludarabine (Flu), 50 mg/kg cyclophosphamide (CY), and 3 Gy total body irradiation (TBI). Cyclosporin A and/or methotrexate were used for graft-versus-host disease prophylaxis. Cord blood grafts were not mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…The use of UCB as the unrelated graft source with RI HSCT for leukemia is a novel approach. Several studies [30][31][32] with other hematological malignancies are encouraging, but disease specific outcomes are inconclusive. Previous UCB studies [33] have shown slower hematopoietic recovery and increased chronic GVHD associated with cord blood transplantation for leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of UCB as the unrelated graft source with RI HSCT for leukemia is a novel approach. Several studies [30][31][32] with other hematological malignancies are encouraging, but disease specific outcomes are inconclusive. Previous UCB studies [33] have shown slower hematopoietic recovery and increased chronic GVHD associated with cord blood transplantation for leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…CBT performed after myeloablative or reduced-intensity preconditioning has contributed to advancing HSCT therapy for these patients and has been extensively investigated, including comparisons of conditioning regimens (Table 3). 3,14,15,26,[28][29][30][31][32][33][34][35][36][37] The reported engraftment rate is 53-93%, and the rate has been improving, possibly owing to the introduction of double-unit CBT. The reported frequency of grade II-IV acute GVHD is 20-44%; the 1-year OS ranges from 33 to 71%, and the TRM at 1 year ranges from 12 to 43%.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced-intensity conditioning (RIC) regimens have emerged as a novel transplantation modality for those patients with the expectation of reducing TRM and increasing survival after allogeneic HSCT. This strategy was recently expanded for quick use with stem cell sources not only from BM or mobilized PB, but also from CB (Barker et al, 2003;Miyakoshi et al, 2004;Chao et al, 2004;Misawa et al, 2006;Brunstein et al, 2007;Komatsu et al, 2007;Majhail et al, 2008;Uchida et al, 2008;Cutler & Ballen, 2009;Horwitz & Chao, 2010). Several studies have reported on CBT using RIC for adult patients with leukemia, and selected studies using mainly single CB unit are detailed in Table 4.…”
Section: Reduced-intensity Conditioning Regimenmentioning
confidence: 99%